Ineffective Absorption? Failure of Direct-Acting Therapy for Chronic Hepatitis C in Cirrhotic Patients With Roux-en-Y Gastric Bypass - Clara Y. Tow MD; John F. Reinus MD (SAGE Publishing, 2019)
In this era of direct-acting antiviral (DAA) therapy for chronic hepatitis C virus (HCV) infection, treated patients have extremely high rates of sustained virologic response to short courses of therapy regardless of stage of fibrosis. Treatment failure is uncommon and often attributed to medication noncompliance or viral resistance to drug. This report describes 2 Child-Pugh-A cirrhotic patients who failed to clear HCV in response to therapy with DAAs. Each patient had Roux-en-Y gastric bypass (RYGB) surgery preceding DAA therapy. RYGB may create multiple barriers to adequate DAA absorption as a result of changes in gastrointestinal physiology. Treatment monitoring and duration should be carefully considered in this unique patient population.